2020
DOI: 10.4081/hr.2020.8368
|View full text |Cite
|
Sign up to set email alerts
|

Brentuximab Vedotin for Refractory Anaplastic Lymphoma Kinase-Negative Anaplastic Large Cell Lymphoma in Leukemic Phase with RUNX3 Overexpression

Abstract: Anaplastic lymphoma kinase (ALK)- negative anaplastic large cell lymphoma (ALCL) is an aggressive CD30-positive non- Hodgkin lymphoma. ALK-ALCL rarely manifests with extensive bone marrow and peripheral blood involvement (known as “leukemic phase”). A 54-year-old woman was diagnosed with ALK-ALCL in leukemic phase, characterized by an extremely poor prognosis. Lymphoma cells in this case showed chromosomal translocation 1p36.1- encoded RUNX3 and overexpression of its protein. She was refractory to CHOP and sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…RUNX3 has been implicated as a tumor suppressor or oncogene in different type of cancers [ 78 ]. We and others demonstrated that RUNX3 is oncogenic and its overexpression is correlated with poor prognosis and drug resistance in NKTL and anaplastic large cell lymphoma (ALCL) [ 17 , 79 , 80 ]. Interestingly, RUNX3 expression is also regulated by super enhancers in EBV-positive malignant B cells [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…RUNX3 has been implicated as a tumor suppressor or oncogene in different type of cancers [ 78 ]. We and others demonstrated that RUNX3 is oncogenic and its overexpression is correlated with poor prognosis and drug resistance in NKTL and anaplastic large cell lymphoma (ALCL) [ 17 , 79 , 80 ]. Interestingly, RUNX3 expression is also regulated by super enhancers in EBV-positive malignant B cells [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, ten cases of leukemic ALK-negative ALCL have been reported prior to the current study: eight (80%) patients had leukemic disease at initial diagnosis and two patients developed a leukemic phase five years and twenty years after initial diagnosis, respectively [ 16 , 19 ]. Most of the reported patients also had bone marrow involvement and/or thrombocytopenia [ 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chromosomal translocations have been reported in three leukemic ALK-negative ALCL cases in the literature. One case had a translocation involving chromosome locus 1p36.1 (including RUNX3 ) and this case showed overexpression of RUNX3 [ 17 ], one case showed t(2;3)(p21;q21) [ 20 ], and one case had an inv(3)(p21q27) [ 34 ]. It is intriguing that four leukemic ALK-negative ALCL cases have harbored translocations involving 3q21-29, and it will be of interest to explore the potentially involved gene(s) on this locus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations